A-44 ImPACT of Amnesia Related Concussions Across Developmental Stages. (18th June 2020) - Unjia, K; Bennett, R; Lashley, L
Abstract: Objective: This study aimed to examine the relationship between developmental stages and concussions that resulted in amnesia as measured by ImPACT. Method: Participants were selected from an archival de-identified sports medicine ImPACT database. The sample (N = 4, 200) was primarily male (62.2%) student athletes with ages ranging from 10 to 25 years. Participants were divided into three groups: Young athletes (n = 1, 400), Adolescent (n = 1, 400), and Adult (n = 1, 400). A One-Way ANOVA was conducted to determine the relationship between age group and prevalence of concussions resulting in anterograde or retrograde amnesia. Results: The One-Way ANOVA revealed significant differences between age group and anterograde F(2, 4197) = 107.449, p < .001 and retrograde amnesia F(2, 4197) = 82.949, p < .001. Bonferroni pairwise comparison revealed the adolescent athlete group experienced more concussions that result in both anterograde and retrograde amnesia compared to young and adult athletes. There was no significant difference between young and adult athletes. Additionally, there is a significant difference regarding total games missed following concussion F(2, 4197) = 117.723, p < .001, with adolescent athletes missing more games compared to young and adult athletes. Conclusions: The findings of this study suggest adolescent athletes tend to experience more amnesia-related concussions compared to young and adult athletes. Additionally, adolescent athletes miss more games following these types of concussions. This study highlights the impact that certain types of concussions have on athletes across the developmental stages. Future research should analyze the cognitive effects of various types of concussions across the developmental stages.